Characterization of hot deformation behavior of Al-Zn-Mg-Mn-Zr alloy during compression at elevated temperature - Yan, Jie; Pan, Qing-lin; Zhang, Xiang-kai; Sun, Xue; Li, An-de; Zhou, Xun (Journal of Central South University, 2017)
The hot deformation behavior of Al-6.2Zn-0.70Mg-0.30Mn-0.17Zr alloy and its microstructural evolution were investigated by isothermal compression test in the deformation temperature range between 623 and 773 K and the strain rate range between 0.01 and 20 s -1 . The results show that the flow stress decreased with decreasing strain rate and increasing deformation temperature. At low deformation temperature (≤673 K) and high strain rate (≥1 s -1 ), the main flow softening was caused by dynamic recovery; conversely, at higher deformation temperature and lower strain rate, the main flow softening was caused by dynamic recrystallization. Moreover, the slipping mechanism transformed from dislocation glide to grain boundary sliding with increasing the deformation temperature and decreasing the strain rate. According to TEM observation, numerous Al 3 Zr particles precipitated in matrix, which could effectively inhibit the dynamic recrystallization of the alloy. Based on the processing map, the optimum processing conditions for experimental alloy were in deformation temperature range from 730 K to 773 K and strain rate range from 0.033 s -1 to 0.18 s -1 with the maximum efficiency of 39%.